Can haptic reinforced VR simulation transform preclinical pulpotomy training? Insights into skill acquisition, student perceptions, and educational impact: randomized controlled trial - Gramatges-Rojas, Anabel; Sittoni-Pino, María Florencia; Flacco, Nicla; Musalem-Dominguez, Oscar; Spinelli, Mercedes; Felszeghy, Szabolcs; Arias-Herrera, Santiago (Frontiers in Oral Health, 2025)
IntroductionPreclinical training in pediatric dentistry is essential for developing the psychomotor and cognitive skills required for procedures such as pulpotomies. Haptic virtual reality simulators (HVRS) are redefining dental training by providing real-time feedback, on-demand objective assessment, and expanded opportunities for skill development—making them powerful complements to traditional mannequin-based methods. However, evidence supporting their effectiveness in pediatric procedures remains limited.MethodsThis randomized controlled study involved 173 third-year dental students who received prior instruction in both HVRS and conventional simulation. Participants were assigned to either a control group (traditional training only) or an experimental group (additional training with the Simodont® HVRS). All students then performed a standardized pulpotomy on a primary molar resin tooth. Performance was assessed across four technical criteria by blinded evaluators. Student perceptions of the HVRS experience were collected through a questionnaire.ResultsNo statistically significant differences were found between groups for cavity shape or conservative opening. However, the test group showed significantly higher scores in roof removal (p < 0.001), while the control group slightly outperformed in pulp chamber configuration (p < 0.033). Overall performance score was slightly higher in the test group, though not statistically significant. Additionally, most students reported that the simulator improved their understanding of the procedure, visual realism, tactile perception, and manual skills, although fewer students felt it enhanced their ability to deroof the pulp chamber. A majority preferred combining haptic simulation with traditional training.ConclusionHVRS enhanced specific technical skills in pulpotomy, especially pulp chamber roof removal, and was positively perceived by students as a complementary tool in pediatric preclinical training.